2010
DOI: 10.1007/698_2009_44
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Azo Dyes in Anaerobic–Aerobic Sequencing Batch Reactors

Abstract: Effluent discharge from textile and dyestuff industries to neighboring water bodies is currently causing significant health concerns to environmental regulatory agencies due to the toxicity, mutagenicity, and carcinogenicity of the dyes and their breakdown products. Therefore, considerable attention has been given to evaluate the removal of dyes during wastewater treatment and in the natural environment. The most widely used dyes in industries are azo dyes, which require an anaerobic and aerobic phases for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…This fact is probably related to the electron-withdrawing nature of the azo bond and their resistance to oxygenases attack. As anaerobic color removal occurs by the way of reduction of the azo dye, which acts a final electron acceptor in the microbial electron transport chain, existing and more effective electron acceptors like oxygen in the medium could act as a limiting factor for dye removal (Çinar and Demiröz 2010 ). Similar results were obtained in studies on pure bacterial strains such as Pseudomonas luteola, Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…This fact is probably related to the electron-withdrawing nature of the azo bond and their resistance to oxygenases attack. As anaerobic color removal occurs by the way of reduction of the azo dye, which acts a final electron acceptor in the microbial electron transport chain, existing and more effective electron acceptors like oxygen in the medium could act as a limiting factor for dye removal (Çinar and Demiröz 2010 ). Similar results were obtained in studies on pure bacterial strains such as Pseudomonas luteola, Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the denitrification process occurred during the first stage, after which RB-5 was reduced, resulting in the incomplete removal of the dye color. However, a previous study reported that the sparging rate of air and H 2 is a significant parameter for achieving high color removal rates in combined systems [37]. This is because the functioning of the anaerobic azo reductase enzyme, which plays a key role in the cleavage of azo bonds, is limited under aerobic conditions, resulting in an insufficient color removal rate.…”
Section: Decolorization Efficiency Under Various Operating Conditionsmentioning
confidence: 99%
“…Moreover, the presence of a dye-decolorizing peroxidase (DyP) shows the potential of the strains to degrade not only azo but also high-redox anthraquinone-based dyes (11). Furthermore, genes were found for deamination, nitrate reduction, desulfonation, and sulfate assimilation, as well as for the degradation of benzoate, catechol, protocatechuate, and gentisate, which play a key role in the aerobic degradation of aromatic compounds (12). These characteristics support the capability of Shewanella sp.…”
Section: Announcementmentioning
confidence: 99%